Oscillatory Noncollinear Magnetism Induced by Interfacial Charge Transfer in Superlattices Composed of Metallic Oxides - Jason D. Hoffman; Brian J. Kirby; Jihwan Kwon; Gilberto Fabbris; D. Meyers; John W. Freeland; Ivar Martin; Olle G. Heinonen; Paul Steadman; Hua Zhou; Christian M. Schlepütz; Mark P. M. Dean; et al. (Physical Review X, 2016)
Interfaces between correlated complex oxides are promising avenues to realize new forms of magnetism that arise as a result of charge transfer, proximity effects, and locally broken symmetries. We report on the discovery of a noncollinear magnetic structure in superlattices of the ferromagnetic metallic oxide La_{2/3}Sr_{1/3}MnO_{3} (LSMO) and the correlated metal LaNiO_{3} (LNO). The exchange interaction between LSMO layers is mediated by the intervening LNO, such that the angle between the magnetization of neighboring LSMO layers varies in an oscillatory manner with the thickness of the LNO layer. The magnetic field, temperature, and spacer thickness dependence of the noncollinear structure are inconsistent with the bilinear and biquadratic interactions that are used to model the magnetic structure in conventional metallic multilayers. A model that couples the LSMO layers to a helical spin state within the LNO fits the observed behavior. We propose that the spin-helix results from the interaction between a spatially varying spin susceptibility within the LNO and interfacial charge transfer that creates localized Ni^{2+} states. Our work suggests a new approach to engineering noncollinear spin textures in metallic oxide heterostructures.